A critical view of the 2nd Social and Economic Cohesion Report and the future of regional policies after 2006 - Marco Lopriore (European Regional Science Association (ERSA), 2001)
The recently published Second Cohesion Report shows the results of development of regions and draws some reflections on the future of regional policies and structural funds. It is important to notice the results of cohesion in European regions and to understand how regions will be compared and benchmarked in the enlarged Europe. How will the relative position of EU regions compare towards CEEC regions ? The Second Cohesion offers already a first view which however should be complemented with other data and information not only on actual problems such as GDP gap, R&D gaps, unemployment but more on mapping trends of solutions to these problems. A wider collection of data available through actors such as CCI, can help complete the picture with trends on demography of businesses, development of ecommerce and SMEs, of networks of excellence, development of industrial districts, etc. Therefore a more dynamic and complete views of how European territories are changing is needed. If future cohesion policies go towards focusing more on horizontal factors of development such as innovation, human resources, infrastrutcure, new technologies, etc then an important role can be played by local actors such as CCI that are able to create consensus among the players and businesses at regional and local level. Regional policies should favour the general interest of businesses rather than a specific sector. Actors such as Chambers of Commerce and Industry can have an important role to play in the process of local economic policies from the partnership in defining priorities of development for territories to the final stages of implementation of measures to support development and growth. Chambers in Italy are carrying out agreements at provincial level in Territorial PActs, at regional level they are concluding agreements with Regional authorities, and at national level they are promoting synergies towards the EU. In France, Chambers are also very active in a new concept of development, i.e. "territoires et pays" and have a long tradition of spatial development. This is also in line with the principle of proximity and subsidiarity which intends to involve actors based not only on delegation of powers in a vertical line of subsidiarity but also on the functions and capacity to carry out certains tasks and their proximity to the end users (businesses or citizens). EU chambers of commerce have signed for this a Charter of cooperation which defines Chambers as actors of local development.
Keywords: 330